Australopapuan leaf beetle diversity: the contributions of hosts plants and geography. Issue 2 (1st December 2016) - Reid, Chris AM
Abstract: The diversity of Chrysomelidae (Coleoptera) in Australia and New Guinea (Australopapua) is reviewed. There are 3100 described species in 244 genera, with a further 2300 species to be described or confirmed. Approximately 11.6% of the world species of Chrysomelidae are found in Australopapua. Among the larger subfamilies, there is a relative dearth of Bruchinae, Cassidinae and Criocerinae and a relative abundance of Chrysomelinae, Cryptocephalinae and Eumolpinae. In the smaller subfamilies, Lamprosomatinae and Synetinae are absent, whereas Sagrinae and Spilopyrinae are strongly represented. Endemicity at generic level is high, exceeding 30% in all subfamilies, except Donaciinae (one species), and exceeding 50% in Chrysomelinae, Cryptocephalinae, Eumolpinae, Sagrinae and Spilopyrinae. The most diverse and ecologically dominant plant orders host the most chrysomelid genera (39 genera on Myrtales, 34 on Fabales, 15 genera on both orders), but many major plant orders in the region, such as Ericales, are almost ignored. Processes contributing to the diversity of Chrysomelidae in Australopapua are discussed, particularly co‐speciation, co‐evolution, dispersal and vicariance.